Oligomer β-amyloid Induces Hyperactivation of Ras to Impede NMDA Receptor-Dependent Long-Term Potentiation in Hippocampal CA1 of Mice - Wang, Ya; Shi, Zhaochun; Zhang, Yajie; Yan, Jun; Yu, Wenfeng; Chen, Ling (Frontiers in Pharmacology, 2020)
The activity of Ras, a small GTPase protein, is increased in brains with Alzheimer’s disease. The objective of this study was to determine the influence of oligomeric Aβ1-42 on the activation of Ras, and the involvement of the Ras hyperactivity in Aβ1-42-induced deficits in spatial cognition and hippocampal synaptic plasticity. Herein, we show that intracerebroventricular injection of Aβ1-42 in mice (Aβ-mice) enhanced hippocampal Ras activation and expression, while 60 min incubation of hippocampal slices in Aβ1-42 (Aβ-slices) only elevated Ras activity. Aβ-mice showed deficits in spatial cognition and NMDA receptor (NMDAR)-dependent long-term potentiation (LTP) in hippocampal CA1, but basal synaptic transmission was enhanced. The above effects of Aβ1-42 were corrected by the Ras inhibitor farnesylthiosalicylic acid (FTS). ERK2 phosphorylation increased, and Src phosphorylation decreased in Aβ-mice and Aβ1-42-slices. Both were corrected by FTS. In CA1 pyramidal cells of Aβ1-42-slices, the response of the AMPA receptor and phosphorylation of GluR1 were enhanced with dependence on Ras activation rather than ERK signaling. In contrast, the Aβ1-42-slices showed dysfunction of NMDA receptor (NMDAR) with the decline of GluN2A/2B phosphorylation, which was recovered by the FTS application and mimicked in control slices treated with the Src inhibitor PP2. The administration of PP2 abolished the protection of FTS against to Aβ-impaired spatial cognition and LTP. However, Aβ-enhanced synaptic transmission was insensitive to the inhibition of MEK or Src. Overall, the results indicate that the oligomeric Aβ1-42 hyperactivates Ras and thereby causes the downregulation of Src which impedes NMDAR-dependent LTP induction resulting in cognitive deficits.